2007
DOI: 10.1039/b614426h
|View full text |Cite
|
Sign up to set email alerts
|

The internal structure of self-assembled peptide amphiphiles nanofibers

Abstract: The self-assembly of peptide amphiphiles (PAs) into nanofibers and their bioactivity as well as physical properties have been investigated by our laboratory over the past few years. We report here on the use of transmission infrared spectroscopy (IR) and polarization modulation-infrared reflection-absorption spectroscopy (PM-IRRAS) to characterize the internal structure of the nanofibers. Depositing nanofibers flat on surfaces, and using the surface selection rules in PM-IRRAS, we demonstrate that peptide amph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
154
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(166 citation statements)
references
References 55 publications
12
154
0
Order By: Relevance
“…1-3, available at www.jneurosci.org as supplemental material). The cylinders have a well defined diameter in the range of 6 -8 nm and consist of ␤-sheet assemblies that tend to be parallel to the nanofibers (Jiang et al, 2007). Because each molecule contains an epitope sequence at its hydrophilic terminus, the nanostructures assembled in an aqueous medium are able to display bioactive sequences perpendicular to their long axis at nearly van der Waals density.…”
Section: Introductionmentioning
confidence: 99%
“…1-3, available at www.jneurosci.org as supplemental material). The cylinders have a well defined diameter in the range of 6 -8 nm and consist of ␤-sheet assemblies that tend to be parallel to the nanofibers (Jiang et al, 2007). Because each molecule contains an epitope sequence at its hydrophilic terminus, the nanostructures assembled in an aqueous medium are able to display bioactive sequences perpendicular to their long axis at nearly van der Waals density.…”
Section: Introductionmentioning
confidence: 99%
“…Self-assembly of PA molecules is further controlled by hydrophobicity of the alkyl tail and hydrogen bonding between adjacent peptides. The morphology of the PA assemblies has been characterized by transmission and scanning electron microscopy techniques (TEM and SEM), atomic force microscopy (AFM), circular dichroism (CD), nuclear magnetic resonance (NMR) and infrared (IR) spectroscopy (Behanna et al 2005;Jiang et al 2007).…”
Section: One-dimensional Assembliesmentioning
confidence: 99%
“…The structural characterization of these supramolecular fibers consisting of β-sheets and hydrophobic collapse is not trivial since they are not crystals but do contain internal order. 29 The mechanical integrity of the PA gels that are formed is also limited due to the absence of any internal covalent bonds connecting the PA monomers. In our original work, we showed that cysteine residues could be used to internally crosslink the nanofibers.…”
Section: Introductionmentioning
confidence: 99%
“…30 More recently, our group has also determined that there is order in the inner hydrophobic core of the nanofibers containing alkyl chains. 29 In the present work, we have placed the diacetylene groups in the hydrophobic alkyl segments and studied the polymerization both as a probe for the nanofiber's internal structure as well as a strategy to obtain novel properties.…”
Section: Introductionmentioning
confidence: 99%